Perinatal Factors Associated With Newborn Survival Of Extremely Low Birth Weight - Chavez, Rossana Cecilia Andrade (2019)
Objective. To determine factors associated with mortality in ELBW infants in the Maternal Perinatal National Institute (INMP). Methods. A case-control study in the NICU of the INMP. We reviewed the medical records of all the ELBW infants, born in INMP since Janaury to December of 2010, which were divided into two groups: group 1 (cases), ELBW infants alive at discharge; group 2 (controls), ELBW infants dead at discharge; both groups sought the factors to which they were exposed. We performed bivariate analysis, calculation from the odd radio with confidence interval of 95% and logistic regression.